Possibilities of using microsoft teams in teaching foreign languages - Solovyova, O. V.; Соловйова, О. В. (ХНУ імені В. Н. Каразіна, 2023)
Modern higher education is being rapidly filled with new means of information technologies, which leads to a change in the ways of providing new material using all available modern educational methods in the conditions of online learning. This format requires finding new or improving and modifying traditional methods and forms of teaching a non-native language to foreigners. Solving the problem of teaching non-native language in the system of either synchronous or asynchronous online learning is a complex and important task. It is impossible to imagine life without new information technologies that help us teach and learn new material, 140 therefore, the development and implementation of electronic forms of training is relevant in increasing the efficiency and quality of education.